2014
DOI: 10.1007/s00415-014-7390-z
|View full text |Cite
|
Sign up to set email alerts
|

How predictors and patterns of stroke recurrence after a TIA differ during the first year of follow-up

Abstract: The highest risk of subsequent stroke after a TIA occurs within the first week after the index event. However, the risk of stroke recurrence (SR) remains high during the first year of follow-up. We studied the temporal pattern and predictors of SR (at 7 days and from 7 days to 1-year follow-up). Between April 2008 and December 2009, we included 1,255 consecutive TIA patients from 30 Spanish stroke centers (PROMAPA study). We determined the short-term (at 7 days) and long-term (from 8 days to 1 year) risk of SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Kernan et al reported that prior stroke was a predictor of recurrent stroke after a TIA or stroke ( 27 ). In the PROMAPA study-a multicenter prospective TIA registry operating from 30 Spanish centers-prior stroke and coronary heart disease were independent predictors of late (from 7 days to 1 year after the onset of a TIA) recurrent stroke after a TIA ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kernan et al reported that prior stroke was a predictor of recurrent stroke after a TIA or stroke ( 27 ). In the PROMAPA study-a multicenter prospective TIA registry operating from 30 Spanish centers-prior stroke and coronary heart disease were independent predictors of late (from 7 days to 1 year after the onset of a TIA) recurrent stroke after a TIA ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 71 studies were included (A. Mowla, MD, unpublished data, 2020). 9 , 15 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ...…”
Section: Resultsmentioning
confidence: 99%
“… 15 , 33 , 34 , 35 , 36 , 37 , 40 , 61 , 67 , 68 , 81 , 85 , 87 , 93 The setting of care was not fully described or the study included the patients who received treatment in various care settings and multiple centers in 37 cohorts (87 303 patients; mean [SD] age, 70.8 [3.8] years, 43 495 of 87 303 [49.8%] men). 27 , 42 , 43 , 44 , 45 , 46 , 47 , 50 , 51 , 53 , 59 , 60 , 62 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 81 , 86 , 88 , 89 , 90 , 92 , 94 Eight studies 9 , 32 , 51 , 52 , 53 , 58 , 59 (and A. Mowla, MD, unpublished data, 2020) provided the outcome of the patients in both inpatient and TIA clinic cohorts. The risk of subsequent stroke was reported for 35 356 patients within 2 days, 36 134 patients within 7 days, 142 185 patients within 30 days, and 94 731 patients within 90 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of patients with cardioembolic stroke remained stable, but the percentage of patients with an undetermined cause who experienced stroke recurrence increased with time after TIA. 22…”
Section: Discussionmentioning
confidence: 99%